Diagnostic Potential of Multidetector Computed Tomography for Characterizing Small Renal Masses - Maria Elisabetta Mancini; Annamaria Albergo; Marco Moschetta; Mariacristina Angelelli; Arnaldo Scardapane; Giuseppe Angelelli (The Scientific World Journal)
Objectives. To assess the potential of CT for characterizing small renal tumors. Methods. 76 patients with <4 cm renal tumors underwent CT examination. The following parameters were assessed: presence of calcifications, densitometry on unenhanced and enhanced scans, washout percentage, urinary tract infiltration, star-shaped scar, and paradoxical effect. Results. Calcifications were found in 7/56 (12.5%) carcinomas. Clear cell carcinomas were as follows: mean density 183.5 HU (arterial phase), 136 HU (portal phase), and 94 HU (delayed phase), washout 34.3%; chromophobe carcinomas were as follows: mean density 135 HU (arterial phase), 161 HU (portal phase), and 148 HU (delayed phase), washout 28%; papillary carcinomas were as follows: mean density 50.3 HU (arterial phase), 60 HU (portal phase), and 58.1 HU (delayed phase), washout 2.7%. In 2/56 (3.6%) cases urinary tract infiltration was found. Oncocytomas were as follows: mean density 126.5 HU (arterial phase), 147.5 HU (portal phase), and 115.5 HU (delayed phase), washout 28.6%. On unenhanced scans, angiomyolipomas were as follows: density values <30 HU in 12/12 (100%) of cases and on enhanced scans: mean density 78 HU (arterial phase), 128 HU (portal phase), and 80 HU (delayed phase), washout 50%. Conclusions. Intralesional calcifications and urinary tract infiltration are suggestive for malignancy, with the evidence of adipose tissue for angiomyolipomas and a modest increase in density with a reduced washout for papillary carcinomas. The intralesional density on enhanced scans, peak enhancement, and washout do not seem significant for differentiating clear cell, chromophobe carcinomas, angiomyolipomas, and oncocytomas.